Pathologic Risk Factor in Retinoblastoma: An Institutional Experience Based on Analysis of Enucleated Eyes - Shah, Anita; Shrestha, Manisha; Shrestha, Saurav Man; Khatri, Anadi; Shrestha, Prateek Krishna (Nepalese Journal of Ophthalmology, 2021)
Background:  Mortality resulting from the metastasis of retinoblastoma is uncommon in the developed world, however it still constitutes a major problem in developing countries like Nepal. The cases of retinoblastoma with increased risk of metastasis even after enucleation can be predicted from the histopathological examination of the enucleated specimen. We conducted this study aiming to assess the frequency and spectrum of high-risk histological features in enucleated specimens of retinoblastoma. Materials and methods: Forty-two specimens of primary enucleation done for treatment of retinoblastoma received in the Department of Pathology at UCMS from 1st January 2016 to 31st December 2018 were included in the study. All slides were reviewed for high-risk histological features along with tumor differentiation, tumor extension, necrosis, and staging. Correlation of high-risk histological features with age and tumor size was calculated using unpaired t-test and correlation with tumor differentiation, necrosis and staging was done using Pearson Chi square test. Results: The median age at enucleation was 24 months. All patients had endophytic lesion with a mean tumor size of 1.8cm. One or more high-risk histological features were identified in 30.9% (13/42). The most common high-risk histological feature was retrolaminar optic nerve invasion (10/12, 71.4%). Statistically significant correlation of high risk histological features was noted with tumor size (p=0.011) and AJCC stage of tumor (p=0.0001). Conclusion: Complete histopathological evaluation of retinoblastoma requires searching for high-risk histological features, the presence of which will guide the clinician in timely planning for subsequent neoadjuvant therapy.